EFISIENSI PENGELOLAAN KEUANGAN DENGAN MENGHITUNG TURNOVER RECEIVABLE PADA PASIEN BPJS KESEHATAN RUMAH SAKIT DAERAH BENOWO SURABAYA - Shafira Panduwinata; Anita Akhirruddin (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The research focuses on the management of patient receivables from the Indonesian Health Security Agency (BPJS) at Hospital in Surabaya from 2019 to 2022. Through financial data analysis, it unveils the fluctuations in receivables turnover and billing periods during this period. The Accounts Receivable Turnover (ART) ratio varied, starting at 6.16 in 2020, peaking at 14.21 in 2021, and decreasing to 8.72 in 2022. These changes reflect the hospital's ability to convert BPJS receivables into cash. Meanwhile, the Average Collection Period (ACP) decreased from 59.25 days in 2020 to 25.69 days in 2021, but rose to 41.86 days in 2022, indicating shifts in the time needed to collect outstanding balances. Challenges arose from rejected BPJS claims affecting receivable balances, compounded by an increase in BPJS patients in 2022. Adapting to BPJS policy changes and streamlining the claim verification process will be crucial for financial stability. This research was conducted using quantitative methods. The research findings state that the financial management at Benowo Regional Hospital in Surabaya is inefficient.